Las debilidades de la etnología marxista - Laura Ibarra (Estudios sobre las Culturas Contemporáneas)
In this article it is suggested that Marxist analysis suffers from various deficiencies when it attempts to explain prehispanic thought. In general, Marxist analysis concentrates on the concerns which the ancient Mexicans articuiated in their worldview, and the function that these concerns fulfilled in their socio-economic system. However, this form of analysis neglects both the conditions under which prehispanic concepts of the world evolved and, more generally, how the acquisition of religions thought is possible. Given that Marxist analysis does not consider the processes tlirough which an understanding and interpretation of the world is constituted, it leaves uiie?q}lained a major part of ancient Mexican thought. This article offers several alternative interpretations based on the perspective of genetic historical theory.